STRATEGI PENGAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS PEMBELAJARAN TEMATIK DI SMA 5 KOTA BENGKULU: STUDI PADA PROGRAM PLP TEMATIK KELOMPOK 73 - Samsudin, Samsudin; Tri Hartanto, Ikhsan; Stefhany Aswandi, Nadiya; Nur Fadillah, Sabillah; Wahyuda, Azi; Yuliani, Alya (Jurnal Ilmu Pendidikan Islam, 2025)
Islamic Religious Education (PAI) learning at SMA 5 Bengkulu City applies a thematic strategy to link Islamic teachings with students' daily lives. This study analyzes teaching strategies, obstacles, and the impact of thematic learning. The research results show that the strategy of integrating religious values, discussions and projects increases students' understanding in cognitive, affective and psychomotor aspects. The main obstacles include a lack of teacher understanding, limited facilities, and student resistance. Teacher training, improved facilities and more interesting strategies are needed for effective learning.